Politeness Strategies In Social Media On Instagram Jennie Blackpink - Sandjaja, Angelina; Afriana, Afriana (Prosiding, 2024)
This descriptive qualitative research identified the politeness strategies in social media on Instagram Jennie Blackpink. It used a theory by Brown and Levinson. This research applied observational method and non-participation technique in collecting the data. The subject of this research was Jennie Blackpink Instagram account. There were positive and negative politeness that have found in this study. The most dominant politeness strategies that the researchers has found is positive politeness